Proof of relationship between xi, yi and x, y in linear regression

Verified

Added on  2023/06/04

|3
|533
|327
AI Summary
The given proof shows the relationship between xi, yi and x, y in linear regression. It also explains the concept of simple linear regression model.
tabler-icon-diamond-filled.svg

Contribute Materials

Your contribution can guide someone’s learning journey. Share your documents today.
Document Page
2. Show that the following relationships holds

i=i
n
( xi x ) ( yi y )=
i=1
n
xi ( yi y ) …………………………. (xx)
Proof
Expand the right hand side of the equation (xx) as follows

i=1
n
( xi x ) ( yi y )=
i=1
n
xi ( yi y )
i=1
n
x ( yi y ) ……………… (i)
Consider the last term

i=1
n
x ( yi y ) =x
i =1
n
( yi y )

i=1
n
x ( yi y ) =x {
i=1
n
yi
i=1
n
y }

i=1
n
x ( yi y ) =x {
i=1
n
yin y } …………………………………………. (ii)
But,
y=

i=1
n
yi
n
, implying n y=
i=1
n
yi…………………………………………...... (iii)
Substitute (iii) in equation (ii) to obtain

i=1
n
x ( yi y ) =x {
i=1
n
yi
i=1
n
yi } = 0
Now equation (i) becomes

i=1
n
( xi x ) ( yi y )=
i=1
n
xi ( yi y ) . Hence proved
3. Show that the following relationships holds

i=1
n
yi =
i=1
n
^yi
Proof
tabler-icon-diamond-filled.svg

Secure Best Marks with AI Grader

Need help grading? Try our AI Grader for instant feedback on your assignments.
Document Page
We know that ei = yi ^yi
Taking summation on both sides

i=1
n
ei=
i=1
n
( yi ^yi )

i=1
n
ei=
i=1
n
yi
i=1
n
^yi ……………………………………………… (i)
But,
i=1
n
ei=¿ 0
Equation (i) becomes
0 ¿
i=1
n
yi
i=1
n
^yi
Then,
i=1
n
yi =
i=1
n
^yi. Hence proved.
4. Show that for the simple linear regression model, the point ( x , y) is always on the
regression line.
Proof
For simple linear regression yi= ^yi + ^ei and ^yi= ^b0 + ^b1 xi
But, y=

i=1
n
yi
n =

i=1
n
( ^yi + ^ei )
n
y=

i=1
n
( ^yi + ^ei )
n
y=

i=1
n
^yi
n

i=1
n
^ei
n
. ……………………………………….. (i)
Since,
i=1
n
^ei=0 equation (i) becomes
Document Page
y=

i=1
n
^yi
n
y=

i=1
n
( ^b0 + ^b1 xi )
n
y=

i=1
n
^b0
n +

i=1
n
^b1 xi
n
y= ^b0 + ^b1

i=1
n
xi
n
……………………………………… (ii)
Since, x=

i=1
n
xi
n
equation (ii) becomes
y= ^b0 + ^b1 x. Therefore, the regression line goes through point ( x , y).
chevron_up_icon
1 out of 3
circle_padding
hide_on_mobile
zoom_out_icon
[object Object]

Your All-in-One AI-Powered Toolkit for Academic Success.

Available 24*7 on WhatsApp / Email

[object Object]